Tourism Gentrification: The Case of Mevlana Museum and its Surroundings - Turker, Nuray (The international journal of religious tourism and pilgrimage, 2024)
Today, residents experience tourism-driven gentrification in many tourist destinations. Gentrification due to tourism has both beneficial economic and physical effects, but it also has a negative impact on a number of sociocultural, physical, and environmental factors. The aim of this study is to explore the physical, economic, and socio-cultural effects of tourism activities in and around Mevlana Museum in Konya, Turkey, which is home to the tomb of the religious figure Mevlana, a symbol of tolerance and peace, from the perspective of tourism gentrification. To this end, a qualitative study was carried out in January 2023 with 15 Konya-based respondents, with content analysis being used to analyse the data. The findings indicate that there have been noteworthy changes in the neighbourhood where the museum is located, as a result of tourism gentrification. The most striking economic and socio-cultural changes created by tourism in the region are the opening of coffee houses, restaurants, souvenir shops and chain hotels, which have increased the economic revenue of local people. The tradesmen’s standard of living improved as a result of this tourism growth. Additionally, physical changes, such as the restoration and re-functioning of old buildings in Mevlana and in its surroundings, have changed the decaying image of the area. Mevlana and its surroundings were transformed into a commercial area, and residents have moved into luxurious apartments.